Students’ Perception of The Challenges in Comprehending the English Language Listening Test - Sidhu, Parveen Sarjit; Sivaguru, Shobhanambigha (Social Sciences, Humanities and Education Journal (SHE Journal), 2023)
Listening is an essential component of the communication process. Of the four primary components of communication skills—reading, listening, speaking, and writing—it is the most crucial one. Therefore, this study was conducted to investigate the students’ perception of the factors that make it challenging to comprehend the "Listening Test" assessment. Eighteen (18) students from the DNS3B class at Politeknik Balik Pulau who took the "Listening Test" assessment for the course DUE 3012, Communicative English 2 participated in this study. Descriptive statistics were used to analyse the data collected via a yes-or-no questionnaire. The result showed that a few major factors influenced the students’ performance in their “Listening Test” assessment. They are; a) Language proficiency level, b) Listening skills, c) Passage length, d) Speech rate, e) Poor audio projection, and f) Testing Conditions. This paper also recommended several implications for practices based on this study and previous research for curriculum designers, teachers/lecturers/instructors and students.